2010
DOI: 10.4085/1062-6050-45.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Ice Hockey Injuries Presenting to US Emergency Departments, 1990–2006

Abstract: Context: Although the number of US ice hockey participants doubled from 1990 to 2006, no nationally representative studies have examined US ice hockey injuries among participants of all ages during this period. Objective: To describe patients with ice hockey injuries presenting to a representative sample of US emergency departments (EDs) from 1990 through 2006. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 21 publications
5
58
0
2
Order By: Relevance
“…Ambulatory Medical Care Survey, National Electronic Injury Surveillance System, and the National Health Interview Survey) showed the NEISS contains the most comprehensive surveillance of injuries treated in the emergency department [11]. The database has been used for various studies [1,3,21,23,24]. Some of these studies use the NEISS to give an in-depth analysis of a specific injury type such as a shoulder dislocation, scaphoid fracture, or an ankle sprain.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory Medical Care Survey, National Electronic Injury Surveillance System, and the National Health Interview Survey) showed the NEISS contains the most comprehensive surveillance of injuries treated in the emergency department [11]. The database has been used for various studies [1,3,21,23,24]. Some of these studies use the NEISS to give an in-depth analysis of a specific injury type such as a shoulder dislocation, scaphoid fracture, or an ankle sprain.…”
Section: Discussionmentioning
confidence: 99%
“…По данным недавно проведенного общенационального американского исследования, сотрясения мозга, связанные в том числе с проведением силовых приемов, более распространены среди лиц в возрасте до 18 лет (9 % всех травм), чем среди более старших спортсменов (3,7 % всех травм). Одна из причин этого заключается в том, что мозг детей и подростков более подвержен черепно-мозговой травме, чем мозг взрослого человека, даже при меньшей силе удара [4].…”
Section: Introductionunclassified
“…1 In their analysis of NEISS data, Deits et al reported that the proportion of head injuries seen at the ED among females was 2.22 times greater than the proportion of head injuries among males. Because 19.9% of the females' injuries were to the head, we can deduce that the proportion of head injuries to males was approximately 9%.…”
Section: A Ratio Of 2 Percentagesmentioning
confidence: 99%
“…It is a useful surrogate of disease risk and can inform the direction of prospective research studies examining risk factors. The limitations of this measure are well described and include the following: (1) No population-at-risk information (denominator) means that diseases or deaths cannot be attributed to actual exposures or risk factors, and (2) the sum of all proportionate causes must equal 1, so any proportion is dependent on the value of all other proportions. 17 In other words, an excess in one cause is offset by a deficit in another cause.…”
Section: Relationship To the Proportional Mortality Ratiomentioning
confidence: 99%
See 1 more Smart Citation